INFLUENCE OF PEASANT MIGRATION ON FORMATION OF A NETWORK OF RURAL SETTLEMENTS OF THE NORTH CAUCASUS - Pavel Petrovich Turun (Вестник Северо-Кавказского федерального университета)
Influence of peasant migration on formation and transformation of a network of rural settlements of the North Caucasus during the pre-revolutionary period is considered in article.